Predictive value of attentional bias for the recurrence of depression: A 4-year prospective study in remitted depressed individuals. (March 2019) - Elgersma, Hermien J.; Koster, Ernst H.W.; Vugteveen, Jorien; Hoekzema, Albert; Penninx, Brenda W.J.H.; Bockting, Claudi L.H.; de Jong, Peter J.
Abstract: Previous research showed that individuals who were remitted from a depressive disorder displayed heightened attention towards negative adjectives (e.g., worthless). We tested if this attentional bias (AB) is predictive of future recurrence of depressive episodes and/or having depressive symptoms at 2- and 4-year follow-up. We used a longitudinal approach within the Netherlands Study of Depression and Anxiety (NESDA) and selected participants who were remitted from Major Depressive Disorder (MDD) (n = 918). AB was measured with a verbal Exogenous Cueing Task; using 2 presentation times (500 and 1250 ms) and 3 stimulus types (negative, positive, neutral). Over 4 years, we prospectively assessed recurrence of depressive episodes and depressive symptomatology after participants completed the ECT. Diagnosis of depressive disorder was measured with clinical rating-scales and self-report questionnaires. A heightened probability of recurrence was neither associated with (heightened) AB for negative nor with (lowered) AB for positive adjectives. Thus, the findings do not support the view that an AB toward negative stimuli or away from positive stimuli plays a critical role in the recurrence of depression. Highlights: Recurrence of MDD was assessed over a 4–year time-period following recovery. AB for negative adjectives did not increase the probability of recurrence of MDD. AB for negative adjectives showed no prognostic value for depressive symptoms at FU. Low AB for positive adjectives did not increase the risk of recurrence. Low AB for positive adjectives showed no prognostic value for symptoms of MDD at FU.